IMPLEMENTASIKAN HAK-HAK MASYARAKAT HUKUM ADAT DALAM PENGUASAAN CAGAR ALAM GUNUNG MUTIS - Agustinus Seo Bani; Saryono Yohanes; Rafael Rape Tupen; Kotan Y. Stefanus (Jurnal Riset Multidisiplin Edukasi, 2026)
The recognition and protection of indigenous peoples’ rights constitute a constitutional mandate as stipulated in Article 18B paragraph (2) of the 1945 Constitution of the Republic of Indonesia. However, in practice, the implementation of these rights continues to face significant challenges, particularly in conservation areas. One such area is the Mount Mutis Nature Reserve in North Central Timor Regency, East Nusa Tenggara Province, which has been traditionally controlled and utilized by the Mollo indigenous community. This study aims to analyze the implementation of indigenous peoples’ rights in the control of the Mount Mutis Nature Reserve and to examine the role of local government and community support in managing the area. The research employs a normative legal research method supported by an empirical approach. Data were collected through literature review of relevant laws and regulations, as well as interviews with government officials, conservation area managers, customary leaders, and local community members in Tasinifu Village, Mutis District. The findings reveal that the Mollo indigenous community maintains strong historical, spiritual, and social ties to the Mount Mutis area, as reflected in the existence of customary sites such as sacred stones (faot kanaf) and sacred water sources (oe fam). Although the rights of indigenous peoples over the area are normatively recognized, their implementation remains suboptimal due to limited administrative recognition, boundary disputes, and conservation management approaches that tend to be top-down. Government support is still partial and has not fully positioned indigenous communities as key actors in conservation area management. This study emphasizes the necessity of strengthening legal recognition of indigenous peoples and developing participatory conservation management models that prioritize indigenous involvement to ensure justice, protection of traditional rights, and environmental sustainability.